(untitled) (The International Journal for Scientific Research, 2026)
This research aims to measure and understand the impact of oil prices on the exchange rate in Iraq, and to identify "it’s positive and negative effects and repercussions, through studying the reality and historical development of oil prices and some monetary variables, using the best modern statistical and econometric programs and tests included in the research". The research reached a number of conclusions, the most important of which is that there is a long-term complementary relationship between the price of oil and the exchange rate of the US dollar in Iraq. The research concluded with a number of recommendations, the most important of which is working to diversify sources of income in Iraq to supply the Iraqi market with foreign currency, the most important of which is the US dollar.